GAMBARAN PENGETAHUAN TENTANG KEPUTIHAN PADA REMAJA PUTRI - Julasmi Eduwan (Universitas Bengkulu, 2022)
About 90% of Indonesian women have the potential to experience vaginal discharge due to Indonesia's tropical climate because it causes fungi to easily breed. Reproductive disorders are the second problem that occurs in women after menstrual disorders. Many negative impacts can occur if women ignore vaginal discharge, one of the effects can be a serious disease such as cancer of the reproductive organs. The purpose of this study was to obtain an overview of knowledge about vaginal discharge in adolescent girls at SMA Negeri 6 Bengkulu City. This study used a descriptive method with a quantitative approach. The population in this study were all students of SMA Negeri 6, totaling 480 students. The sample in this study amounted to 144 respondents, sampled using the quota sampling technique. Collecting data using a questionnaire with 20 questions distributed via a google form. The results of this study there are 49 respondents (34%) with good knowledge, 69 respondents (48%) with sufficient knowledge, and 26 respondents (18%) with less knowledge. Suggestions from the results of this study can be used as a reading, input, and reference in conducting further research on vaginal discharge with different variables, to increase this knowledge such as organizing counseling by education about reproductive health, especially vaginal discharge in women.